2013
DOI: 10.1158/1535-7163.mct-12-0998
|View full text |Cite
|
Sign up to set email alerts
|

The HSP90 Inhibitor NVP-AUY922 Potently Inhibits Non–Small Cell Lung Cancer Growth

Abstract: Heat shock protein 90 (HSP90) is involved in protein folding and functions as a chaperone for numerous client proteins, many of which are important in non-small cell lung cancer (NSCLC) pathogenesis. We sought to define preclinical effects of the HSP90 inhibitor NVP-AUY922 and identify predictors of response. We assessed in vitro effects of NVP-AUY922 on proliferation and protein expression in NSCLC cell lines. We evaluated gene expression changes induced by NVP-AUY922 exposure. Xenograft models were evaluated… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(41 citation statements)
references
References 49 publications
2
39
0
Order By: Relevance
“…S2). Nevertheless, knockdown of HSP90a and b, two major isoforms of HSP90 that are inhibited by AUY922 (25,26), similarly inhibited survival of HCT116 and SW620 but not WiDr and Caco-2 cells (Fig. 1F).…”
Section: Resultsmentioning
confidence: 92%
“…S2). Nevertheless, knockdown of HSP90a and b, two major isoforms of HSP90 that are inhibited by AUY922 (25,26), similarly inhibited survival of HCT116 and SW620 but not WiDr and Caco-2 cells (Fig. 1F).…”
Section: Resultsmentioning
confidence: 92%
“…The Hsp90 inhibitor ganetespib, alone or in combination with other anticancer drugs, displays effective antitumor effects in lung cancer cells, especially lung cancer harboring mutant K-Ras (Acquaviva et al, 2012). Another Hsp90 inhibitor, NVP-AUY922 [(5Z)-N-ethyl-5-(4-hydroxy-6-oxo-3-propan-2-ylcyclohexa-2,4-dien-1-ylidene)-4-[4-(morpholin-4-ylmethyl) phenyl]-2H-1,2-oxazole-3-carboxamide], has also shown potent antiproliferative and antitumor effects in various lung cancer cells (Garon et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, Hsp90a protein was one of 12 proteins used as a panel for lung cancer diagnosis, which were generated by a new aptamer-based proteomic analysis of 1,326 archived serum samples from four independent studies of NSCLC in long-term tobacco-exposed populations (16). Other previous studies showed the HSP90 inhibitor had a potent antitumor activity in in vitro and in vivo models of therapy against NSCLC (17,18). Our current study further demonstrates that detection of plasma Hsp90a protein could be useful as a biomarker for diagnosis of lung cancer and for therapeutic monitoring of responses of patients with lung cancer.…”
Section: Discussionmentioning
confidence: 99%